Effect of Clenbuterol Administration into the Basolateral Amygdala on Synaptic Plasticity in Dentate Gyrus Granule Cells in Male Rats - Seyedeh Kebria Noorani; Vida Hojati; Motahareh Rouhi Ardeshiri; Esmaeil Akbari (Journal of Mazandaran University of Medical Sciences, 2021)
Background and purpose: Neural circuits and neurotransmitter systems within the basolateral amygdala (BLA) play roles in forming emotional memory through communication with the hippocampus. Therefore, in this study, the role of these neural circuits on synaptic plasticity was investigated by agonist injection of beta-adrenergic receptors into the BLA. Materials and methods: In this experimental study, the electrophysiological recording from the hippocampus was investigated. Male Wistar rats (210-250 gr) were divided into two groups: control group that received saline (0.5 μl) and the treatment group that received clenbuterol (10 ng/0.5μl). Clenbuterol was also bilaterally injected into the BLA. Then, we studied the effect of clenbuterol on basal activity of the granular cells of the dentate gyrus (DG). Afterwards, a 200-Hz high-frequency stimulation protocol was applied to induce long-term potentiation (LTP). The amplitude of the population spike (PS) and the slope of the excitatory post synaptic potential (EPSP) were analyzed before and after the injection of clenbuterol. Results: Injection of clenbuterol (10 ng) did not increase PS of the LTP compared to the control group in the DG region. Also, no significant increase was seen in the slope of EPSP in treatment group compared to the control group (P>0.05). Conclusion: Clenbuterol administration into the basolateral amygdala (10 ng/0.5μl) did not affect basal electrical activity and synaptic reinforcement of the dentate granular cells in 90 minutes